2011
DOI: 10.1111/j.1365-2893.2011.01477.x
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of IgM antihepatitis A virus and IgM antihepatitis E virus in acute viral hepatitis: a prospective, multicentre study in Korea

Abstract: This study investigated the clinical, serological and molecular characteristics of coexistence of both immunoglobulin M (IgM) antihepatitis A virus (HAV) and IgM antihepatitis E virus (HEV) in acute viral hepatitis using a prospective, multicentre design. Among a total of 771 symptomatic cases with acute viral hepatitis enrolled in a Korean city from September 2006 to August 2008, coexistence of IgM anti-HAV and IgM anti-HEV was found in 43 patients (A+E group; 6%), while the existence of IgM anti-HAV alone wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…17-20 In the interpretation of HEV serological test, we should consider the possibility of false-positive result especially in nonendemic areas. The detection of IgM anti-HEV in serial samples as well as serum or stool HEV RNA detection is helpful to confirm diagnosis 21. Two Korean cases of genotype 4 hepatitis E reported in 2010 and 2011 are similar to our case with a nucleotide similarity of 97 and 98%, respectively 8,22.…”
Section: Discussionsupporting
confidence: 65%
“…17-20 In the interpretation of HEV serological test, we should consider the possibility of false-positive result especially in nonendemic areas. The detection of IgM anti-HEV in serial samples as well as serum or stool HEV RNA detection is helpful to confirm diagnosis 21. Two Korean cases of genotype 4 hepatitis E reported in 2010 and 2011 are similar to our case with a nucleotide similarity of 97 and 98%, respectively 8,22.…”
Section: Discussionsupporting
confidence: 65%
“…The investigators hypothesized that alternative infectious agents may cause cross-reactivity of HEV EIAs, resulting in false positives. Other research has demonstrated EIA cross reactivity between EBV and CMV [1314], hepatitis A [15], and HIV [1617], suggesting a ‘molecular mimicry’ phenomenon. Our findings of a significant association between HIV and HEV IgM positivity, lack of HEV RNA, and lower rates of HEV EIA positivity among healthy control residents may be suggestive of such a process.…”
Section: Discussionmentioning
confidence: 99%
“…In the 1980 s, 62% of patients with acute viral hepatitis were infected with HBV [Lee et al, ]. This has now decreased to approximately 5% of recent acute viral hepatitis cases in Korean adults [Choi et al, ; Jang et al, ]. In addition, the majority of acute hepatitis B patients in the early 1980 s were aged 10–29 years.…”
Section: Discussionmentioning
confidence: 99%